Elastographic Region of Interest Determination for Muscle with Fat Infiltration - Yuri, Takuma (Clin Interv Aging, 2021)
PURPOSE: Ultrasound elastography has been used to evaluate the skeletal muscle stiffness as a biomarker for sarcopenia assessment. However, there is no consensus with respect to the size and location of the region of interest in assessing such fat infiltrated muscle. The objective of this study was to determine which cross-sectional area should be measured in torn disuse muscle with fat infiltration to accurately measure muscle activity using real-time tissue elastography (RTE). METHODS: Twenty-seven patients, whose rotator cuff muscle with torn tendon was successfully repaired, were followed by programmed rehabilitation. RTE measurements of the supraspinatus muscle were obtained during muscle contraction before and one-year after surgery so that the activity value was defined as the difference between elastography measurements at rest and elastography measurements during contraction. Given that the patients with successfully repaired and completed rehabilitation showed an increased activity value, the sensitivity for three regions of interest; posterior portion of the anterior-middle subregion (AM-p), anterior region (AR), and whole cross-sectional area of the supraspinatus (whole) were compared with the number of patients showing an increase in activity values as sensitivity analysis. RESULTS: The sensitivity showing an increase in activity values was 74.1% for the AM-p area, 70.4% for the AR area, and 81.5% for the whole area. Intraclass correlation coefficient(1,3) was 0.87–0.97 for the AM-p area, 0.88–0.98 for the AR area and 0.92–0.99 for the whole area. CONCLUSION: The whole cross-sectional area is suitable to measure muscle activity in muscle with fat infiltration. The results in this study will provide some beneficial information when ultrasound elastography is used for the assessment of sarcopenia muscle with fat infiltration.